2014
DOI: 10.1371/journal.pone.0087705
|View full text |Cite
|
Sign up to set email alerts
|

Immune Monitoring of the Circulation and the Tumor Microenvironment in Patients with Regionally Advanced Melanoma Receiving Neoadjuvant Ipilimumab

Abstract: We evaluated neoadjuvant ipilimumab in patients with surgically operable regionally advanced melanoma in order to define markers of activity in the blood and tumor as assessed at baseline (before ipilimumab) and early on-treatment. Patients were treated with ipilimumab (10 mg/kg intravenously every 3 weeks ×2 doses) bracketing surgery. Tumor and blood biospecimens were obtained at baseline and at surgery. Flow cytometry and immunohistochemistry for select biomarkers were performed. Thirty five patients were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
231
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(246 citation statements)
references
References 37 publications
(39 reference statements)
14
231
1
Order By: Relevance
“…Tarhini et al (2014) observed a potent CD4 + and CD8 + antigen-specific T cell immunity against testicular cancer (NY-ESO-1) and melanocytic lineage (MART-1, gp100) antigens. Tumour-infiltrating CD3 + CD4…”
Section: Mdscs As a Target For Diseases Of Ageingmentioning
confidence: 98%
See 1 more Smart Citation
“…Tarhini et al (2014) observed a potent CD4 + and CD8 + antigen-specific T cell immunity against testicular cancer (NY-ESO-1) and melanocytic lineage (MART-1, gp100) antigens. Tumour-infiltrating CD3 + CD4…”
Section: Mdscs As a Target For Diseases Of Ageingmentioning
confidence: 98%
“…Cancer Ipilimumab (CTLA4 antagonist) was used by Pico de Coaña et al (2014) and Tarhini et al (2014) in patients with melanoma and was shown to reduce MDSCs in both studies, but for Tregs, a decrease and increase were reported respectively. Tarhini et al (2014) observed a potent CD4 + and CD8 + antigen-specific T cell immunity against testicular cancer (NY-ESO-1) and melanocytic lineage (MART-1, gp100) antigens.…”
Section: Mdscs As a Target For Diseases Of Ageingmentioning
confidence: 99%
“…In advanced melanoma patients, immune therapy based on pharmacologically blocking CTLA-4 on Tregs, can be monitored by an increase of circulating CD4(+) and CD8(+) T cell lymphocytes 64,65 . We have found that advanced stages melanoma show statistically higher circulating CD19(+) B lymphocytes with no increase in plasma level of total Igs and/or Igs subclasses.…”
Section: Circulating Immune Cellsmentioning
confidence: 99%
“…15,16 Moreover, evidences of modification of the balance between effector and regulatory immune responses, involving myeloid derived suppressor cells (MDSCs) and regulatory T cells (Treg), both in the circulation and in tumor infiltrates were reported in association with the clinical activity of IPI. 2,17,18 Along this line, the increase of the absolute leukocyte cell count (ALC) or of circulating CD4 C T cells expressing the inducible co-stimulatory molecule (ICOS) have been documented in relation with anti-CTLA-4 mAb therapies. 12,[19][20][21] ICOS C T cells that were augmented by IPI therapy in tumor lesions from prostate cancer patients, represented lymphocytes endowed with antitumor activity.…”
Section: Introductionmentioning
confidence: 99%